High-Mobility Group Box-1 and Its Potential Role in Perioperative Neurocognitive Disorders - Sarah Saxena; Véronique Kruys; Raf De Jongh; Joseph Vamecq; Mervyn Maze (Cells, 2021)
Aseptic surgical trauma provokes the release of HMGB1, which engages the innate immune response after binding to pattern-recognition receptors on circulating bone marrow-derived monocytes (BM-DM). The initial systemic inflammation, together with HMGB1, disrupts the blood–brain barrier allowing penetration of CCR2-expressing BM-DMs into the hippocampus, attracted by the chemokine MCP-1 that is upregulated by HMGB1. Within the brain parenchyma quiescent microglia are activated and, together with the translocated BM-DMs, release proinflammatory cytokines that disrupt synaptic plasticity and hence memory formation and retention, resulting in postoperative cognitive decline (PCD). Neutralizing antibodies to HMGB1 prevents the inflammatory response to trauma and PCD.